2018
DOI: 10.1016/j.media.2018.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Algorithms for left atrial wall segmentation and thickness – Evaluation on an open-source CT and MRI image database

Abstract: HighlightsAn open-source atrial wall thickness CT and MRI dataset (n=20) with consensus ground truth obtained with statistical estimation from expert delineation (n=2).Exploring a range of metrics for evaluating and ranking wall segmentation and thickness algorithms (n=6), and benchmarks were set on each metric.New three-dimensional mean thickness atlases for atrial wall thickness derived from the consensus ground truth. The atlas was also transformed into a two-dimensional flat map of thickness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 52 publications
(72 reference statements)
0
76
0
Order By: Relevance
“…Secondly, the quantification of scars in our work is performed on the surface mesh projected from the LA endocardium. Karim et al (2018) discussed the importance of wall thickness, particularly considering the potential that the ectopic activity can prevail in scars that are non-transmural. However, they also emphasized that the relationship between the AF and the changes in wall thickness was not clear, and the thickness was difficult to measure based on current MRI data.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the quantification of scars in our work is performed on the surface mesh projected from the LA endocardium. Karim et al (2018) discussed the importance of wall thickness, particularly considering the potential that the ectopic activity can prevail in scars that are non-transmural. However, they also emphasized that the relationship between the AF and the changes in wall thickness was not clear, and the thickness was difficult to measure based on current MRI data.…”
Section: Discussionmentioning
confidence: 99%
“…This is likely due to the limited relevant public datasets as well as the difficulty of the task. In addition, to the best of our knowledge, there are very few works that apply deep learning techniques to atrial wall segmentation, as also suggested by a recent survey paper (Karim et al, 2018). In the following sections, we will describe and discuss these methods regarding different applications in detail.…”
Section: Cardiac Mr Image Segmentationmentioning
confidence: 99%
“…On comparing the computational speed for different multi-atlas methods for automatic CTA segmentation, whereas some groups [8], [9], [14], [17], [29] did not report the computational time, those groups that did [5]- [7], [10], [12], [15], [18] required a much longer processing time (greater than five minutes) than our method (less than three minutes). The processing voxel size is unsurprisingly one of the key factors influencing the overall segmentation time.…”
Section: Discussionmentioning
confidence: 79%
“…For the WH segmentation, Funka-Lea et al [25] proposed a graph-cuts method, Zheng et al [26] presented a marginal space learning method, and van Rikxoort et al [5] proposed a multiatlas based segmentation technique. Likewise, Jolly [27] proposed a graph-cuts and EM-based method to segment the LV, Karim et al [17] segmented the LA, Yang et al [8] segmented the LV and LVM, and Tobon et al [9] segmented the LA and PA only.…”
Section: Previous Workmentioning
confidence: 99%